Paradoxes of Democracy and Depoliticisation in the Social Peripheries of Modernity - Preite, Gianpasquale (PARTECIPAZIONE E CONFLITTO, 2018)
At the end of the 20th Century, the global diffusion of economic neoliberalism represents, seen from diverse perspectives, the outcome of a communicative overlapping between the economic system and the political system. This overlapping is equivalent to a functional intrasparency, which generates paradoxes of democracy as the depoliticisation and exclusion phenomena when facing inclusion expectations, as occurs in the peripheries of the world. Depoliticisation, in fact, appears as a paradox of democratic systems closely related to the development of the technocratic practices and the enhancement of the bureaucratic apparatus. One of the characteristics of technocracy is that it lies on the assumption that great decisions are of technical nature, not political. If great decisions may be taken by means of technical instruments, it means that there is no longer need for 'professional politicians', and even less need for people's participation. Technocracy and burocracy converge above the traditional sphere reserved to politics. The consequence of this convergence is, in fact, depoliticisation. In other words, there is a relation between technocracy, burocracy and ideological crises. Hence, the more technical the decision-making process, the more burocratized will the process of power be, and the more deideologized will the process of fundamental choices be. Populist movements thus describe the effect of the attempt of providing responses to the issues of modern society, to the extent in which the economic value becomes the only discriminating variable between what is correct and what is wrong (what is economically pointless must be discarded) and it actually move the decisional process away from the political sphere, enhancing the differences between the center and the periphery, between inclusion and exclusion. In the light of such trends, which have become extensively resilient in the systems, how can the process of functional specification of social systems (economics, politics) be implemented in the peripheries of modernity? If trust in the political system lessens vis à vis problem-solving capabilities, how the consequent uncertainty be absorbed? This essay aims to describing the extent in which the depoliticisation process can compensate for the pressure put on expectations against inclusion values. The theme is tackled with an outlook that stems from the epistemological mutation of globalization and, consequently, from the resolution of the traditionally axial center/periphery pattern, and focuses on the analysis of peripheries that come into play as the protagonists of the two-way relationship with their center, albeit the unusual democratic participation, yet to be interpreted.